2015
DOI: 10.1007/s00264-015-3013-2
|View full text |Cite
|
Sign up to set email alerts
|

Hip-joint congruity after Dega osteotomy in patients with cerebral palsy: long-term results

Abstract: Data of our study with high plasticity of the hip joint suggest that even if the femoral head is deformed and a persistent incongruency after surgery is expected, hip reconstruction can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The CE angle also increased after surgery, suggesting a better coverage of the acetabulum over the femoral head. This replicates the findings of previous studies [ 30 , 31 ]. Although this is partly attributed to the pelvic osteotomy, some previous reports have suggested that femoral osteotomy itself may have some effects on acetabular development [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The CE angle also increased after surgery, suggesting a better coverage of the acetabulum over the femoral head. This replicates the findings of previous studies [ 30 , 31 ]. Although this is partly attributed to the pelvic osteotomy, some previous reports have suggested that femoral osteotomy itself may have some effects on acetabular development [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to forces acting on the femoral head from the lateral portion of the acetabulum and the surrounding muscles. Braatz et al [ 29 , 30 ] reported that even when the femoral head is deformed pre-operatively, the plasticity of the hip joint allows for the remodelling of the femoral head from aspherical to spherical. Braatz et al [ 29 , 30 ] also reported an improvement in congruency of the hip joint after surgery, with a further improvement at the long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 95% of the hips remained reduced and there were no redislocations. Braatz et al 33 reported the outcomes after the combined procedure in 72 hips in patients with cerebral palsy. In their study, at a mean follow-up of 7.7 years, 89% of hips had an MI less than 30%, which is similar to a another previous report.…”
Section: Discussionmentioning
confidence: 99%
“…Orthopedic surgery can roughly be divided into tendon lengthening, tendon transfer, osteotomy, and arthrodesis. The indications include fixed contracture, joint deformity, joint dislocation, and subluxation that affect function or cause pain [18][19][20][21][22]. Furthermore, the purpose of surgery is to improve motor function, prevent deformity, relieve pain, and modify the appearance of patients [23,24].…”
Section: Surgical Managementmentioning
confidence: 99%